2023
DOI: 10.1039/d3cp02214e
|View full text |Cite
|
Sign up to set email alerts
|

The magnetically induced current density of the [12]infinitene dianion

Qian Wang,
Mesías Orozco-Ic,
Dage Sundholm

Abstract: The magnetically induced current-density susceptibility (MICD) of the [12]infinitene dianion and the induced magnetic field around it have been calculated at the density functional theory level. Separation of the MICD...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, for helical structures, interpretations of aromaticity based on magnetic shielding functions differ from the insights gained through current− density computations. [13][14][15]27 Namely, B z ind displays a deshielding cone, which is typical for antiaromatic systems, whereas the NICS calculations predict an aromatic character, which is evident through the formation of shielding cones at all 6-MRs. The differences originate due to the helical structure, in which the induced current density flows along the perimeter of the helicenes.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…However, for helical structures, interpretations of aromaticity based on magnetic shielding functions differ from the insights gained through current− density computations. [13][14][15]27 Namely, B z ind displays a deshielding cone, which is typical for antiaromatic systems, whereas the NICS calculations predict an aromatic character, which is evident through the formation of shielding cones at all 6-MRs. The differences originate due to the helical structure, in which the induced current density flows along the perimeter of the helicenes.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The NICS function has been commonly used to discuss aromaticity in three-dimensional systems because, unlike B z ind , it is a quantity that does not depend on the orientation of the external magnetic field. However, for helical structures, interpretations of aromaticity based on magnetic shielding functions differ from the insights gained through current–density computations. , Namely, B z ind displays a deshielding cone, which is typical for antiaromatic systems, whereas the NICS calculations predict an aromatic character, which is evident through the formation of shielding cones at all 6-MRs. The differences originate due to the helical structure, in which the induced current density flows along the perimeter of the helicenes. , It is these changes in the direction of the current–density flux in conjunction with the orientation of the rings with respect to the external field that causes the in-plane x - and y -components of B ind to become important. , Therefore, NICS(0) and B z ind (0) calculations provide a different aromatic nature for each ring of the studied molecules.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…X-ray crystal structure analysis has shown that the combined lamellar and herringbone-like packing structure introduced three-dimensional electronic interactions caused by the infinity shape. Since this report, fascinating properties of infinitene have been predicted. Wu and Isobe et al synthesized a twisted CNB in 2021 and a fused [5]helicene dimer in 2023 , as a related molecule of infinitene. In addition to aromatic hydrocarbon-based CNBs, heteroatom-embedded CNBs have also been reported. In 2019, Tanaka et al synthesized the first oxygen-embedded CNB by rhodium-catalyzed alkyne cyclotrimerization .…”
Section: Synthesis Of Cnbs and Related Aromatic Beltsmentioning
confidence: 99%